Pengaruh Likuiditas, Leverage, dan Profitabilitas Terhadap Financial Distress: Peran Moderasi Ukuran Perusahaan - Hafizi, Mohamad; Azazi, Anwar; Rosnani, Titik; Mustika, Uray Ndaru (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to examine the effect of liquidity, leverage, and profitability on financial distress, with firm size as a moderating variable. The sample consists of 30 consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023, selected through purposive sampling. Data were analyzed using Moderated Regression Analysis (MRA) based on the Fixed Effect Model (FEM) with the assistance of EViews 12 software. The findings indicate that leverage has a significant positive effect on financial distress (p < 0.01), while liquidity and profitability do not show significant effects (p > 0.05). Firm size negatively moderates the relationship between liquidity and financial distress (β = –0.626; p < 0.05) and positively moderates the effect of profitability (β = –3.422; p < 0.05), but does not moderate the influence of leverage. These results emphasize the importance of internal company characteristics—particularly firm size—in shaping the financial impact of key financial ratios. Theoretically, this research contributes to the development of a more comprehensive financial distress prediction model, while practically, it provides strategic insights for companies in formulating more adaptive financial risk mitigation efforts.